2020
DOI: 10.1093/jxb/eraa120
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effect of two herbicide resistance mutations on acetolactate synthase kinetics and growth traits

Abstract: Gene mutations conferring herbicide resistance are hypothesized to have negative pleiotropic effects on plant growth and fitness, which may in turn determine the evolutionary dynamics of herbicide resistance alleles. We used the widespread, annual, diploid grass weed Alopecurus aequalis as a model species to investigate the effect of two resistance mutations—the rare Pro-197-Tyr mutation and the most common mutation, Trp-574-Leu—on acetolactate synthase (ALS) functionality and plant growth. We characterized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…Our prediction results showed that different AHAS mutations had different levels of herbicide resistance, and in most cases, the herbicide resistance level of multi-point mutations was higher than that of single-point mutations (Table ). These results were consistent with the previously published literature. ,,,, Target-site resistance, caused by the mutation of the key amino acid of a target enzyme, is the most common mechanism leading to resistance to an AHAS inhibitor . Currently, at least 28 resistance-endowing amino acid substitutions at eight conserved positions in the AHAS enzyme have been identified in weed biotypes with field-evolved resistance .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our prediction results showed that different AHAS mutations had different levels of herbicide resistance, and in most cases, the herbicide resistance level of multi-point mutations was higher than that of single-point mutations (Table ). These results were consistent with the previously published literature. ,,,, Target-site resistance, caused by the mutation of the key amino acid of a target enzyme, is the most common mechanism leading to resistance to an AHAS inhibitor . Currently, at least 28 resistance-endowing amino acid substitutions at eight conserved positions in the AHAS enzyme have been identified in weed biotypes with field-evolved resistance .…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with the previously published literature. 9,14,34,35,45 Target-site resistance, caused by the mutation of the key amino acid of a target enzyme, is the most common mechanism leading to resistance to an AHAS inhibitor. 9 Currently, at least 28 resistance-endowing amino acid substitutions at eight conserved positions in the AHAS enzyme have been identified in weed biotypes with field-evolved resistance.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, this study reports for the first time the Trp‐2027‐Leu substitution of ACCase conferring cyhalofop‐butyl resistance in weed species. The rarity of Trp‐2027‐Leu of ACCase may be partially due to its possible adverse pleiotropic effects on plant growth by changing enzyme functionality 42,43 . A dCAPS marker was then successfully developed to specifically detect the Trp‐2027‐Leu mutation in Leptochloa chinensis without performing gene sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in codons 197 and 574 are considered to be important points for ALS inhibitors ( Powles & Yu, 2010 ; Tranel et al, 2019 ; Zhao et al, 2020 ). Trp-574-Leu has the ability to develop resistance to all groups of ALS inhibitor herbicides ( Pandolfo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%